SPECIAL FEATURES OF BUDECTON DRUG - Axmedov Shamshod Jamshidovich; Ergashov Bekhruzjon Komilovich (Ta’lim innovatsiyasi va integratsiyasi, 2024)
The drug exhibits an anti-inflammatory effect, so it should be used continuously and regularly even after the patient’s condition improves. As a rule, Budecton is prescribed for a long course of treatment, which is determined individually. Sometimes, due to the large amount of bronchial secretion, access of the drug to the area of ​​inflammation may be difficult. In such cases, a preliminary short course of treatment with oral corticosteroids is recommended.